The Efeect of Marketplace on Consumer Satisfaction of Shopee Platform in Jember District, Indonesia - Muhammad Syarofi; Rusmini Rusmini; Utrotul Mu’allimah; Mukhamad Roni (JOURNAL OF SHARIA ECONOMICS, 2022)
Marketplace is a new business model that develops along with the evolution of IT infrastructure (Information Technology). The existence of a marketplace makes consumptive people prefer to spend their money to buy a desired product quickly and easily. This has something to do with consumer satisfaction, consumer satisfaction is the level of one’s feelings after comparing the expected performance or product results with expectations. Shopee is a marketplace with monthly visitors which from the 3rd quarter of 2019 to the fourth quarter of 2020 experienced a continuous increase. However, in the first quarter of 2021, shopee experienced a decrease in monthly visitors from 129.3 million visitors to 127.4 million visitors. This made Tokopedia one rank above Shopee with 135.1 million visitors. This survey was conducted to determine the influence of the marketplace on consumer satisfaction on the Shopee platform in Jember District. This was quantitative research with the type of survey research. The population used was the people of Jember District, with purposive sampling technique, while the formula used to determine the number of samples was using the Cochran formula. The data collection used questionnaire method and measuring variables with a Likert scale. Analysis of research data with inferential tests include t test (partial), F test (simultaneous), R2 test (coefficient of determination), and multiple linear regression test. This research concluded that 1) The marketing mix had no significant effect on consumer satisfaction, the value of tcount was 1.857 < ttable 1.980. 2) Human resources did not have a significant influence on consumer satisfaction, the tcount value was 1.557 < ttable 1.980. 3) Information technology had a significant influence on consumer satisfaction, the value of tcount was 2,040 > ttable 1,980. 4) Expedition had a significant effect on consumer satisfaction, the tcount value was 3.735 > ttable 1.980. 5) The marketing mix, human resources, information technology, and expeditions simultaneously had a significant effect on customer satisfaction with the Fcount 28.505 > Ftable 2.47, the R Square value was 0.545 or 54.5%